Case Report: White Colored Stool: An Early Sign of Cystic Fibrosis in Infants - Jing Guo; Rong He; Zhi-qin Mao (Frontiers in Pediatrics, 2021)
A 2-month-old male infant presented with white colored stools 1 month after birth. There was no jaundice of the skin, mucous membrane, or sclera; his liver was enlarged (4 cm below the ribs), and his liver function tests showed slightly elevated total bilirubin (TB), direct bilirubin (DB), and total bile acid (TBA). An abdominal doppler ultrasound showed no signs of biliary atresia. Genetic testing revealed a CFTR hemizygous mutation site (c.223C>T) in exon 3 and exon 2–3 heterozygous deletion mutation. The infant's stool turned yellow after oral administration of pancreatic tablets. Finally, the infant was diagnosed with cystic fibrosis (CF). Review of literature revealed five children (including the infant in this case study) with CF who presented with white stool. All five children had anemia, four had edema and hypoproteinemia, five had changes in stool color (it was pistachio-green color in two patients, pale colored in one, acholic stool in one, and white stool in one), two had cholestasis, one infant had delayed meconium discharge, and three children had delayed growth and hepatomegaly. Two children had an abnormal sweat test, one had a F508del compound heterozygous mutation, and one had three mutation sites (C.214G>G/A, P.A72T; C.650A>A/G, P.E217G, and C.3406G>G/A, P. A1136T), which was a compound heterozygous mutation. So, CF could be included in the differential diagnosis of infants with white stool. Genetic testing could confirm an early diagnosis of CF. Pancreatic replacement therapy has been shown to be beneficial for improving the digestive function.